Genistein: A Potential Natural Lead Molecule for New Drug Design and Development for Treating Memory Impairment - Fuloria, Shivkanya; Muhamad Azrul, Amir Yusri; Mahendran, Sekar; Gan, Siew Hua; Nur Najihah, Izzati Mat Rani; Lum, Pei Teng; Ravi, Subban; Vetriselvan, Subramaniyan; Abul Kalam, Azad; Jeyabalan, Srikanth; Wu, Yuan Seng *; Meenakshi, Dhanalekshmi Unnikrishnan; et al. (MDPI, 2022)
Genistein is a naturally occurring polyphenolic molecule in the isoflavones group which is well known for its neuroprotection. In this review, we summarize the efficacy of genistein in attenuating the effects of memory impairment (MI) in animals. Scopus, PubMed, and Web of Science databases were used to find the relevant articles and discuss the effects of genistein in the brain, including its pharmacokinetics, bioavailability, behavioral effects, and some of the potential mechanisms of action on memory in several animal models. The results of the preclinical studies highly suggested that genistein is highly effective in enhancing the cognitive performance of the MI animal models, specifically in the memory domain, including spatial, recognition, retention, and reference memories, through its ability to reduce oxidative stress and attenuate neuroinflammation. This review also highlighted challenges and opportunities to improve the drug delivery of genistein for treating MI. Along with that, the possible structural modifications and derivatives of genistein to improve its physicochemical and drug-likeness properties are also discussed. The outcomes of the review proved that genistein can enhance the cognitive performance and ameliorate MI in different preclinical studies, thus indicating its potential as a natural lead for the design and development of a novel neuroprotective drug.